Current Insights into Liver Fibrosis: Epidemiological Patterns, Etiopathogenesis, Clinical Correlates, and Research Agenda - Amedeo Lonardo; Mohamad Jamalinia; Ralf Weiskirchen (Livers, 2026)
Liver fibrosis is the common pathway through which chronic liver injury progresses to cirrhosis, portal hypertension, liver failure, hepatocellular carcinoma, and systemic complications. Its burden is increasing worldwide, driven mainly by metabolic dysfunction-associated steatotic liver disease, alcohol-related liver disease, viral hepatitis, and cardiometabolic comorbidity. Current evidence supports a clinically practical approach centered on early risk recognition, non-invasive fibrosis assessment, etiologic treatment, lifestyle and metabolic risk reduction, and timely referral of patients with suspected advanced fibrosis. Although advanced cirrhosis may remain only partly reversible, fibrosis can regress when the injurious stimulus is controlled, making prevention of progression a realistic therapeutic goal. This review provides a clinically actionable framework for the assessment, management, and prevention of liver fibrosis, integrating current insights into epidemiological trends, etiopathogenesis, non-invasive and portal-hypertension assessment, sex-specific effects, hepatic and extrahepatic outcomes, and treatment strategies. It highlights the potential for fibrosis regression when the underlying etiologic factor is controlled and emphasizes the stages (F0–F2) at which reversibility is most achievable. Additionally, the paper outlines key research priorities to address current knowledge gaps in biomarker discovery, precision medicine, and artificial intelligence-assisted risk stratification, while defining priorities for personalized screening, multidisciplinary care, and combination antifibrotic research.